Potensial Ekstrak Etanol Daun Rambusa (Passiflora foetida L) sebagai Antibakteri: Potential Ethanol Extracts of Rambusa Leaves (Passiflora foetida L) as Antibacterial - Evi Mulyani; Husna Fauzia; Bersiani Bersiani (Jurnal Surya Medika (JSM), 2022)
(Passiflora foetida L) as a wild plant found in shrubs, it has potential as a drug; phytochemical, it has been proven that Rambusa contains secondary metabolites and functions as a drug. This study was conducted to determine the potential of ethanol extract of rambusa leaves in inhibiting the growth of Staphylococcus epidermidis bacteria. This test was carried out using the Kirby-Bauer method with disc paper at concentrations of 5%, 10%, 15%, and 20%. The test results showed that the ethanolic extract of the leaves of Rambusa (Passiflora foetida, L) had potential as an antibacterial in the resistant to intermediate category. Each concentration formed an inhibition zone of 10 + 1.73 mm in sequence; 9.33 + 0.57 mm; 12.66 + 3.21 mm; and 19 + 2.64 mm.